MosSCI and gateway compatible plasmid toolkit for constitutive and inducible expression of transgenes in the C. elegans germline. - Eva Zeiser; Christian Frøkjær-Jensen; Erik Jorgensen; Julie Ahringer (PLoS ONE)
Here we describe a toolkit for the production of fluorescently tagged proteins in the C. elegans germline and early embryo using Mos1-mediated single copy insertion (MosSCI) transformation. We have generated promoter and 3'UTR fusions to sequences of different fluorescent proteins yielding constructs for germline expression that are compatible with MosSCI MultiSite Gateway vectors. These vectors allow tagged transgene constructs to be inserted as single copies into known sites in the C. elegans genome using MosSCI. We also show that two C. elegans heat shock promoters (Phsp-16.2 and Phsp-16.41) can be used to induce transgene expression in the germline when inserted via MosSCI transformation. This flexible set of new vectors, available to the research community in a plasmid repository, should facilitate research focused on the C. elegans germline and early embryo.